2012
DOI: 10.1104/pp.112.198556
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interactions between Carotene Ring Hydroxylases Drive Lutein Formation in Plant Carotenoid Biosynthesis    

Abstract: Plant carotenoids play essential roles in photosynthesis, photoprotection, and as precursors to apocarotenoids. The plastidlocalized carotenoid biosynthetic pathway is mediated by well-defined nucleus-encoded enzymes. However, there is a major gap in understanding the nature of protein interactions and pathway complexes needed to mediate carotenogenesis. In this study, we focused on carotene ring hydroxylation, which is performed by two structurally distinct classes of enzymes, the P450 CYP97A and CYP97C hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 36 publications
5
73
0
Order By: Relevance
“…S4). The relatively low level of ER:LUT1 transorganellar complementation may be attributable to poor interaction of the enzyme with the ER cytochrome P450 reductase or the inability of ER-localized LUT1 to form complexes with other plastid-resident carotenoid biosynthetic enzymes (15,16).…”
Section: Demonstration Of Transorganellar Complementation With Additimentioning
confidence: 99%
“…S4). The relatively low level of ER:LUT1 transorganellar complementation may be attributable to poor interaction of the enzyme with the ER cytochrome P450 reductase or the inability of ER-localized LUT1 to form complexes with other plastid-resident carotenoid biosynthetic enzymes (15,16).…”
Section: Demonstration Of Transorganellar Complementation With Additimentioning
confidence: 99%
“…Carotenoid metabolons (enzyme complexes) are predicted to exist on the basis of high molecular weight complexes containing PSY or other carotenoid enzymes (Maudinas et al, 1977;Camara et al, 1982;Kreuz et al, 1982;Al-Babili et al, 1996;Bonk et al, 1997;Lopez et al, 2008). A recent study showed that the capacity for enzymes to interact was associated with enhanced carotenoid pathway activity (Quinlan et al, 2012). Metabolon-associated enzymes could facilitate substrate channeling, as has been suggested by the absence of carotenoid pathway intermediates, except in cases where the pathway is artificially blocked (Wurtzel, 2004).…”
Section: Open Questions On Metabolon Organization and Dynamicsmentioning
confidence: 99%
“…A phylogenetic analysis with the deduced amino acid sequence (616 amino acids) confirmed its identity as carrot CYP97A3 ( Figure 5A). This was concluded from the high sequence identity to several cytochrome P450 enzymes, which were functionally confirmed as b-ring-specific a-carotene hydroxylases, e.g., from tomato (Sl-CYP97A29, 76% identity; Stigliani et al, 2011), rice (Os-CYP97A4, 69% identity; Quinlan et al, 2012), and Arabidopsis CYP97A3 (71% identity; alignment in Supplemental Figure 6). In contrast, the sequence exhibited only 41% identity to e-ring-specific carotene hydroxylases, including carrot CYP97C1, and branched-off separately in phylogenetic analysis, excluding that the sequence obtained represented an additional CYP97C1 copy ( Figure 5A).…”
Section: Cloning Of Cyp97a3 From White Carrotsmentioning
confidence: 99%